Tiban Trenggalek Art In Max Scheler's Hierarchy Of Values Perspective - Munawir Muslih Mashuri (Eduvest - Journal of Universal Studies, 2024)
Humans living in mukabumi cannot be separated from the name of value, especially in Javanese society. One of the arts that still exists today is the Tiban art in Trengalek Re gency. This art continues to be held every year, especially if the rain does not arrive. The purpose of this study is to examine more deeply the value contained in Tiban art in the perspective of Max Scheler's hierarchy of values. This research uses interpretation method through literature study approach. The results obtained in this study, Tiban art which is an art born from the Mataraman region of Java contains four hierarchies of values, namely the value of pleasure, the value of vitality, spiritual value, and the value of purity.